2022
DOI: 10.1021/acs.energyfuels.2c00854
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Pore Attributes of Sub-Bituminous Gondwana Coal from the Damodar and Wardha Valleys: Implication for Enhanced Coalbed Methane Recovery

Abstract: With the increasing drive for geological CO2 sequestration, unconventional resources like shale gas and coalbed methane have gained massive popularity. With a vast resource of bituminous Gondwana coal, India has a good potential for enhanced coalbed methane recovery through CO2 sequestration. Pore attributes and their interconnectivity play a significant role in determining the gas storage capacity and ease of injection/production. In this study, samples from both opencast and underground measures were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Several researchers have provided the similar correlation and fitted the curve with the coefficient of determination ( R 2 ). , Wang et al showed a correlation between the fractal dimension and the TOC content, mineral matters, and pore structure parameters. It reveals a good correlation for the BET surface area and a negative correlation with the average pore diameter, while no correlation has been shown between the TOC content, mineral matter, and fractal dimension.…”
Section: Discussionmentioning
confidence: 93%
“…Several researchers have provided the similar correlation and fitted the curve with the coefficient of determination ( R 2 ). , Wang et al showed a correlation between the fractal dimension and the TOC content, mineral matters, and pore structure parameters. It reveals a good correlation for the BET surface area and a negative correlation with the average pore diameter, while no correlation has been shown between the TOC content, mineral matter, and fractal dimension.…”
Section: Discussionmentioning
confidence: 93%
“…For the selected experimental setup, the available Q-range was between 0.04 and 1.5 nm −1 . Raw data files obtained are processed using MATSAS Matlab module by Rezaeyan et al 62 Details of calculation are also mentioned in Chandra et al 17,23 Fractal dimension derived from the SAXS can be described with the following equation 17 (6) where D S is surface fractal dimension calculated from SAXS data and A is the slope of I(Q) versus Q plot. 2).…”
Section: Determination Of Organic and Mineral Compositionmentioning
confidence: 99%
“…For the selected experimental setup, the available Q-range was between 0.04 and 1.5 nm −1 . Raw data files obtained are processed using MATSAS Matlab module by Rezaeyan et al 62 Details of calculation are also mentioned in Chandra et al 17,23 Fractal dimension derived from the SAXS can be described with the following equation 17…”
Section: Determination Of Organic and Mineral Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-pressure gas adsorption is a well-established method for characterizing pore structure, which has been applied to characterize the pore structure of shale samples in previous studies. The pore size distribution is calculated using capillary condensation based on the Kelvin Equation in the pore through gas adsorption/desorption . Nitrogen adsorption at 77 K is the standard method for analyzing pore sizes, which is highly accurate for mesopores and macropores in shale samples .…”
Section: Experimental Studies On Shale Microstructure Analysismentioning
confidence: 99%